The purposes, practices, and professionalism of teacher reflectivity : insights for twenty-first-century teachers and students - Pultorak, Edward G., 1961- (Rowman & Littlefield Education, 2010)
Very little information about the impact of reflection on teacher performance, teacher retention, and student learning is available in teacher preparation programs. This book provides practical and research-based chapters that offer greater clarity aboutthe particular kinds of reflection that matter and avoids talking about teacher reflection generically, which implies that all kinds of reflection are of equal value. This book addresses five very pertinent concepts: (1) teacher reflectivity in theory andresearch, (2) teacher reflectivity in teacher education programs, (3) teacher reflectivity.